MEMBANGUN LINGKUNGAN BELAJAR PENDIDIKAN AGAMA ISLAM: PENDEKATAN TEORI EKOLOGI BRONFENBRENNER - Yazid Al Bastomi; Abdul Muhid (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study aims to explore the concept of the Islamic educational environment through the lens of Bronfenbrenner’s Ecological Theory. A systematic literature review was conducted on various relevant academic sources to identify the elements of the Islamic educational environment and analyze them within the framework of Bronfenbrenner’s five levels of ecological systems (microsystem, mesosystem, exosystem, macrosystem, and chronosystem). The results of the study indicate that elements such as the family, madrasah, peers (in an Islamic context), religious teachers, and the mosque are part of the microsystem. The mesosystem involves interactions between these microsystems, such as the family-madrasah and family-mosque relationships. The exosystem encompasses external factors that influence the microsystem, such as parents’ workplaces and Islamic community organizations. The macrosystem consists of Islamic cultural values and religious norms, government policies regarding Islamic education, and the global Muslim community. Finally, the chronosystem reflects the influence of the passage of time and socio-historical events. This framework provides a comprehensive understanding of the complexity of the Islamic educational environment and the implications of Bronfenbrenner’s Ecological Theory in analyzing the various factors that contribute to the development of Muslim individuals. This study contributes to a deeper understanding for educators, policymakers, and researchers in designing more holistic and effective approaches to Islamic education.